2018
DOI: 10.1017/s1742170518000479
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of abrasive weeding in organic grain and vegetable crops

Abstract: Weed competition, especially within the crop row, limits the productivity and profitability of organic crop production. Abrasive weeding, a mechanical alternative to hand weeding, uses air-propelled grits to control small weed seedlings growing within the crop row. Recent research has demonstrated the successful use of abrasive weeding to reduce weed competition and increase yields in organic maize (Zea mays), tomato (Solanum lycopersicum) and green and red pepper crops (Capsicum annuum), but the profitability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In summary, weed suppression and increased potential for crop N uptake achieved by combining abrasive weeding with polyethylene or bioplastic mulch films resulted in increased sweet red pepper yield. A partial budget analysis of this system in Wortman et al (2018) suggests that this yield increase represents a mean net income gain of $33,265/ha relative to the weedy control in plastic mulch. However, the analysis also indicated that organic farmers could increase net income by an additional $38,458/ha if all weeds were removed from the crop row by hand weeding (i.e., the weed free control).…”
Section: Resultsmentioning
confidence: 99%
“…In summary, weed suppression and increased potential for crop N uptake achieved by combining abrasive weeding with polyethylene or bioplastic mulch films resulted in increased sweet red pepper yield. A partial budget analysis of this system in Wortman et al (2018) suggests that this yield increase represents a mean net income gain of $33,265/ha relative to the weedy control in plastic mulch. However, the analysis also indicated that organic farmers could increase net income by an additional $38,458/ha if all weeds were removed from the crop row by hand weeding (i.e., the weed free control).…”
Section: Resultsmentioning
confidence: 99%
“…However, this conversion can be successful only if applications of abrasive grits actually control weeds with reasonable efficacies and costs for labor and materials. Although grit-weeding may be economically favorable in some high-value organic horticultural crops (Wortman et al, 2020), our work with aronia berries transplanted into landscape fabric can address only some of these issues. Hazelnut shell grit did control weeds with efficacies and time allotments similar to those of manual weeding (i.e., hand-hoeing), of which the latter would be a form of weed control prevalent on organic farms.…”
Section: Aronia Berry Field Trialmentioning
confidence: 99%
“…However, labor for handweeding is limited and is progressively becoming more expensive. Although abrasive weeding can reduce labor by 66%, the cost of abrasive grits is very high and the efficiency of this technique is very low as it does not involve automated weed detection [5]. More efficient weed control options are needed for vegetable plants.…”
Section: Introductionmentioning
confidence: 99%